PENGARUH SIKAP BELAJAR SISWA TERHADAP HASIL BELAJAR PKn KELAS VII DAN VIII DI SMP NEGERI 2 BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Rahayu, Sri; ', Gimin; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is background  by the learning attitude of student in SMP Negeri 2 Batu gajah Kecamatan Pasir Penyu Kabupaten Indragiri Hulu. Learning attitude change can be observed in the learning process, objectives, firmness and consistency towards something. This change is one indicator of the success of teachers in implementing the learning process. For that educators must create a lesson plan including the learning experience of students who made the attitudes of learning towards subjects become more positive.The formulation of the problem of this research is "How influence learning  attitudes toward the learning results of PKN VII and VIII class in the SMP 2 Batu Gajah Kecamatan Pasir Penyu Kabupaten Indragiri Hulu?. This study aims to determine how the influence of students' attitudes toward learning result  PKN class VII and VIII in the SMP 2 Pasir Penyu. This research is useful for the reader to add insight and information about the attitude of learning. This research method is quantitative descriptive. The data collection instrument used in this study is a questionnaire consisting of 23 statements about students' attitudes (variable X) and the learning result  of grades (Y). Data were analyzed using linear regression. hypothesis that "there is influence students' attitudes learning result  PKN class VII and VIII in the SMP 2 Pasir Penyu is accepted.". This is evidenced by a series of simple regression test between the variables X and Y, obtained Fhitung 4,43 and 4,00 Ftabel value obtained from the study of the distribution list Ftable with N = 59, at significance level of 5%, thus F count> F table, or 4.43> 4.00. So the hypothesis in this study is accepted that there is a significant impact learning' attitudes toward learning result  PKN class VII and VIII in the smp 2 Batu Gajah Kecamatan Pasir Penyu Kabupaten Indragiri Hulu. Key words: Influence,learning attitude, learning result PKn